2012
DOI: 10.1111/ele.12021
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐diversity in temperate and tropical forests reflects dissimilar mechanisms of community assembly

Abstract: Site-to-site variation in species composition (β-diversity) generally increases from low- to high-diversity regions. Although biogeographical differences in community assembly mechanisms may explain this pattern, random sampling effects can create this pattern through differences in regional species pools. Here, we compared assembly mechanisms between spatially extensive networks of temperate and tropical forest plots with highly divergent species pools (46 vs. 607 species). After controlling for sampling effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
466
7
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(533 citation statements)
references
References 50 publications
44
466
7
5
Order By: Relevance
“…These findings seemingly contradict those of Myers et al [32], who showed that environmental factors played a stronger role in driving species turnover in a temperate compared with a tropical region. Our results may differ because of the different taxa among the two studies, i.e.…”
Section: Discussioncontrasting
confidence: 94%
“…These findings seemingly contradict those of Myers et al [32], who showed that environmental factors played a stronger role in driving species turnover in a temperate compared with a tropical region. Our results may differ because of the different taxa among the two studies, i.e.…”
Section: Discussioncontrasting
confidence: 94%
“…Testing predictions regarding how seed dispersal should influence patterns of seedling species turnover among gaps has proven difficult, since beta diversity varies substantially among forests and at different spatial scales (2,40). Studies suggest that dispersal should decrease species turnover among sites by moving propagules greater distances and reducing the spatial aggregation of species, leading to less clumped distributions (2, 4, 40), but there have been no empirical tests of this for plants.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have observed a greater than expected intraspecific spatial aggregation of tree species in several recent studies from different regions (e.g., De Cáceres et al 2012;Kraft et al 2011;Mori et al 2013). Myers et al (2013) explained how the local ecological mechanisms that cause intraspecific aggregation observed across regions can vary widely between different biogeographical regions (i.e., tropical vs. temperate forests). To quantify the relative contributions of spaceand environment-based assembly processes, their study relied on the null model proposed by Kraft et al (2011).…”
Section: Abundance-driven Sampling Effectsmentioning
confidence: 95%
“…Recently, after carefully disentangling the spatial and environmental factors that contribute to β-diversity, Myers et al (2013) found that tree communities in tropical and temperate forests are most influenced by dispersal limitations and environmental filtering, respectively. Researchers have observed a greater than expected intraspecific spatial aggregation of tree species in several recent studies from different regions (e.g., De Cáceres et al 2012;Kraft et al 2011;Mori et al 2013).…”
Section: Abundance-driven Sampling Effectsmentioning
confidence: 99%
See 1 more Smart Citation